Comparative studies of inhibitory and antioxidant activities, and organic acids compositions of postbiotics produced by probiotic Lactiplantibacillus plantarum strains isolated from Malaysian foods - Chang, Hui Mei; Foo, Hooi Ling; Loh, Teck Chwen; Lim, Eric Teik Chung; Abdul Mutalib, Nur Elina (Frontiers Media, 2021)
Despite inflammation being a protective natural defense against imbalance stressors in the body, chronic inflammation could lead to the deterioration of immune response, low production, and poor performance in livestock as well as severe economic losses to the farmers. Postbiotics produced by Lactiplantibacillus plantarum has been reported recently to be a natural source of antioxidant, promoting growth performance, anti-inflammation, and immune responses. However, the effects of fermentation media on the compositions of L. plantarum postbiotic have not been reported elsewhere. Hence, a comparative study was conducted to compare the volatile compounds, organic acid composition, and antioxidant and antimicrobial activities of postbiotics produced by six strains of L. plantarum cultivated by using formulated media and the commercial de Man, Rogosa, and Sharpe (MRS) medium as a control. Postbiotics RG14, RI11, and UL4 produced by using formulated media exhibited higher inhibitory activity against Pediococcus acidilactici 446, Escherichia coli E-30, Salmonella enterica CS3, and vancomycin-resistant Enterococci except for Listeria monocytogenes LS55. As for the antioxidant activity, hydroxyl radical scavenging activity was enhanced in formulated media, whereas reducing power activity was the highest in postbiotic RI11. Three organic acids, namely, acetic acid, caproic acid, and lactic acid, were detected in the postbiotic produced by various L. plantarum strains. The concentration of acetic acid was influenced by the fermentation media, whereas caproic acid was detected as the highest in postbiotic RG11. Lactic acid was the predominant compound detected in all the postbiotics and had the significantly highest concentration in postbiotic RS5 when produced by using the MRS medium. Intermediary and pyrrole compounds were the other main compounds that were detected by using GC-MS. Positive correlations were found between organic acid production and inhibitory activity, as well as antioxidant activity exhibited by postbiotics. In conclusion, the compositions and functional characteristics of postbiotics produced by the six strains of L. plantarum were strain-dependent and affected greatly by the fermentation medium. The effects of postbiotic composition on the functional characteristics of postbiotics were elucidated in this study to warrant their applications as a promising beneficial natural growth promoter for the livestock industry.